2008
DOI: 10.1089/ten.tea.2007.0293
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic Derivatives of Embryonic Stem Cells Seeded into 3D Polycaprolactone Scaffolds Generated Cartilage TissueIn Vivo

Abstract: In spite of recent scientific advances, treatment and repair of cartilage using tissue engineering techniques remains challenging. The major constraint is the limited proliferative capacity of mature autologous chondrocytes used in the tissue engineering approach. This problem can be addressed by using stem cells, which can self-renew with greater proliferative potential. Cartilage tissue engineering using adult mesenchymal stem cells derived from bone marrows has met with limited success. In this study we exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…Previous studies have reported that implantation of ESCs or ESC-derived chondrogenic cells promoted cartilage repair in vivo [4][5][6]. However, it is difficult to obtain autologous ESCs for cell transplantation, and an immunologic barrier prevents in vivo long-term engraftment and function of allogenous ESCs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that implantation of ESCs or ESC-derived chondrogenic cells promoted cartilage repair in vivo [4][5][6]. However, it is difficult to obtain autologous ESCs for cell transplantation, and an immunologic barrier prevents in vivo long-term engraftment and function of allogenous ESCs [7].…”
Section: Introductionmentioning
confidence: 99%
“…118 EB-derived hESCs seeded onto polycaprolactone scaffolds did not yield a high density of chondrogenic cells, 119 while hiPSCs from OA patient-derived synovial cells have been shown to form cartilage in a 3D PCA scaffold. 120 An alternative is to use natural or synthetic hydrogels in which the cells can be homogenously distributed before gel polymerisation and that are highly permeable though lacking in the strength under load of rigid scaffolds.…”
Section: Figmentioning
confidence: 99%
“…In another example, a scaffold made from polycaprolactone (PCL) was used. EBs were formed in a serum-containing medium including retinoic acid, then outgrowth culture was performed in a serum-containing chondrogenic medium, and the outgrowth cells were seeded onto the PCL scaffold (Fecek et al, 2008). Implantation of the resulting constructs yielded a poor result, with only a few chondrocyte clusters inside.…”
Section: Cooperation With Tissue-engineering Technologymentioning
confidence: 99%